An OpenEHR repository based on a native XML database - Velte, Linda (2013)
OpenEHR is an open standard specification that describes the management, storage, retrieval and exchange of data in Electronic Health Record (EHR). Despite its growing importance in the field, the lack of open source solutions is hindering a larger visibility. In this paper we present an openEHR-based repository supported by a native XML database, which allows to store and query OpenEHR records through the DB service layer and a set of REST web services. The obtained results highlight the efficiency of this API and show that it can be used as a persistence component in any OpenEHR solution.